A study of alteration and mineralisation at the Mace Mo-Cu Porphyry deposit, Ireland - LAVERY, SHANE (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2019)
The Mace molybdenum-copper (Mo-Cu) deposit in the west of Ireland has been explored since the early 1960s, but remains poorly understood in terms of classic porphyry style systems. Knowledge of porphyry systems in general has greatly improved in the past few decades, and this knowledge can now be applied to better understand the nature of Mo-Cu mineralisation at Mace. This thesis presents new reflected and transmitted light petrographic descriptions, geostatistical analyses, laboratory analyses including SEM and LA-ICP-MS, and field relations, to define a new paragenetic sequence of events that have affected the Mace deposit. The deposit is hosted in the Galway Granite, a large and complex body of granitic rocks, outcropping along the northern shore of Galway Bay and extending inland for c.20km. The Galway Granite is a composite batholith; available geochronological data indicate that emplacement occurred between c.423Ma and c.385Ma, with most granites emplaced between c.410 and c.400Ma. Molybdenite from Mace Head has been directly dated using the Re-Os isotope system to 407?1.5Ma. Molybdenum in the deposit occurs as molybdenite, and copper as chalcopyrite, both finely disseminated and concentrated in veins. Mineralisation is predominantly structurally controlled, with a south-southwest to north-northeast orientation. Mineralised veins can be seen at surface, particularly along the coast, where the rocks are well exposed in outcrop. East-southeast to west-northwest faults have been mapped, which appear to cut and dextrally offset the deposit and associated mineralised zones, indicating that they post-date early mineralisation. It is apparent that this persistent east-southeast to west-northwest structural trend provided a weakness for exploitation by mineralising fluids within a preferential orientation, and subsequently a locus for fault displacement. This is particularly evident in the central ?Bog Zone? on the eastern shore of Lough Bunacliffa, which is offset by the Narrow Waters Fault, a major local structural control on mineralisation. The offsets are not significant, being in the order of no more than tens of metres. Extensional quartz-pyrite veins were co-magmatic, or close to coeval with pluton emplacement, and mark the first vein set in the sequence at Mace. Pyrite in these veins contains elements (e.g. cobalt, nickel, selenium) with clear oscillatory zonation patterns, linking their growth to late magmatic fluid. These extensional veins generally do not contain Mo-Cu mineralisation, but are commonly cross-cut by chalcopyrite- and molybdenite-bearing veins. Several generations and types of alteration are evident at the Mace deposit, including potassic, propylitic, and phyllic alteration, which as a whole are typical of porphyry deposits. Mineralisation and alteration at Mace are inherently linked. A high Cu:Mo ratio in assay results is thought to be associated with proximity to the source of mineralisation, due to a combination of high chalcopyrite and molybdenite content in mineralised veins in the deposit and disseminated chalcopyrite associated with potassic alteration in the host granite. In general, strong potassic alteration is indicative of proximity to the core of porphyry deposits, therefore a high Cu:Mo ratio may be regarded as a reliable vector of mineralisation. The Cu:Mo ratio decreases from potassic into propylitic alteration zones, due to a decrease in modal proportion of finely disseminated chalcopyrite in the groundmass. At Mace, propylitic alteration is characterised by an epidote-chlorite assemblage, which is usually interpreted as a distal alteration style in porphyry deposits. The identification of propylitic alteration at Mace is, however, complicated by superimposed phyllic alteration seen as sericite replacement of potassium feldspar and associated with remobilisation of molybdenite in large quartz veins and angular quartz vein breccias. Quartz veins and breccias are associated with some of the highest molybdenum assays seen in drilling to date. Phyllic alteration is commonly observed in the upper level of porphyry systems, suggesting the Mace deposit represents the upper-middle level of a porphyry deposit. A series of dacite dykes intruded the pluton from early in its history through to post-mineralisation, and are not thought to be related to mineralising fluids. Late calcite-fluorite-chlorite veins were intruded post-mineralisation and mark the final hydrothermal event at Mace Head. These veins do not host economic minerals and clearly overprint all other observed vein types. The deposit may contain further concentrations of economic mineralisation at depths below those drilled to date.
APPROVED
Keywords: Economic Geology; Porphyry; Molybdenum; Copper; Ireland